Non-Enzymatic Browning Kinetics in Sucrose-Glycine Aqueous and Dehydrated Model Systems in Presence of mgcl2 - Matiacevich, S (Elsevier Ltd, 2018)
The development of non-enzymatic browning in the presence of MgCl2 was evaluated in liquid and dehydrated sucrose-glycine model systems, in relation to interactions of the salt with water and/or with sucrose. In both systems, browning was accelerated by the presence of MgCl2 because of the increased sugar hydrolysis (ten times faster) and the reduction of water mobility (1H NMR T2 relaxation times) caused by this salt (between 6 and 14% lower), counteracting the inhibitory effect of water on the Maillard reaction. MgCl2 also provoked a 40% reduction on the fluorophores quantum yield, responsible also of the fluctuations observed in the fluorescence development as a function of time after 50 h at 70 °C. Molecular and supramolecular effects of the presence of MgCl2 have been observed on the Maillard reaction kinetics. These results are of high technological interest when strategies to control the Maillard reaction rate are required for a particular application. © 2018